State of the literature discussing smoke-free policies globally: A narrative review - Jacqueline A. Teed; Meagan O. Robichaud; Michelle Duren; Hebe N. Gouda; Ryan David Kennedy (Tobacco Induced Diseases)
Despite the success of the Framework Convention on Tobacco Control (FCTC), most jurisdictions in the world do not have policies that create 100% smokefree environments in indoor workplaces, indoor public places, public transport, or other public places. We conducted a narrative review of articles that discuss smoke-free policies and describe the state of the current literature. A search of peer-reviewed and gray literature, published between 1 January 2004 and 30 April 2022, was conducted using PubMed and EMBASE databases. We classified articles based on the location of the policy discussed (WHO region, World Bank income classification) and the environment that was being made smoke-free. Insights related to policy development and implementation, as well as compliance and enforcement, were also identified. The search identified 4469 unique citations; 134 articles met the criteria for inclusion and underwent data extraction by two independent coders. The sample included articles published in or about jurisdictions in each WHO region, in high- and low- and mediumincome countries, and articles that discussed policies regulating smoke-free indoor workplaces, indoor public places, public transport, outdoor/quasi-outdoor environments, and other (unspecified) public places. Some important insights from the literature related to smoke-free policy implementation included tobacco industry interference, the important role of civil society, and the need for effective communication, education, and leadership. Enforcement officials’ awareness and training, stakeholders’ attitudes and beliefs, and understanding social norms were identified as relevant determinants of effective smoke-free policies. There continue to be challenges for implementing smoke-free policies in jurisdictions throughout the globe, in high- and low- and middle-income countries. The literature includes insights to support 100% smoke-free policies in each environment that must be made smoke-free as per the FCTC.